Aprendizagem e competências empreendedoras: estudo com gestores de tecnologia da informação na região metropolitana de Fortaleza – CE - Silva, Julio Cesar Pereira da (2014)
This study aims to analyze the process of entrepreneurial learning and its influence on entrepreneurial skills developed by the managers of Information Technology in the metropolitan area of Fortaleza - CE. Was adopted as conceptual research models the model of Politis (2005), in the aspect of entrepreneurial learning and the Man and Lau (2000), in the aspect of entrepreneurial competence. The research adopted the qualitative method of descriptive nature. For its implementation, interviews were conducted with ten managers of Information Technology, with the support of a semi-structured questionnaire. The data collected was used the method of content analysis thematic nature. The survey results showed that entrepreneurial learning has paper medium, continuous and experiential in the improvement of entrepreneurial skills of the IT manager. For previous experiences in business influence in the development of initials entrepreneurial skills: administrative, opportunity, commitment and relationship of the IT manager. And were being improved in the continuous process of new experiences with business, both in their early ventures as working then in third. The two modes of transformation of entrepreneurial career experiences, both the exploitation (pre-existing knowledge) as the exploration (new opportunities) influence and improve the development of entrepreneurial skills. Also identified himself continuous and reciprocal influence on the development and improvement of the entrepreneurial skills. Regarding the exercise of entrepreneurial competence commitment, this influences the development of strategic entrepreneurial competence. While the action of conceptual entrepreneurial competence, influences the development of entrepreneurial skills: strategic and opportunity. And the exercise of strategic entrepreneurial competence noted the influence in the development of entrepreneurial skills: administrative, commitment and relationship.